Pengaruh Kepemilikan Manajerial Dan Kepemilikan Institusional Terhadap Nilai Perusahaan - Astari Dianty (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
The main objective of this study is to obtain empirical evidence about the effect of managerial ownership and institutional ownership on firm value in manufacturing companies listed on the Indonesia Stock Exchange. The data population was 154 manufacturing companies in the period 2015 - 2019. The sample was taken by purposive sampling, where only 92 companies met the requirements. The data analysis used in this study was testing classical assumptions and multiple regression analysis. Research partially proves that Managerial Ownership and Institutional Ownership have an effect on Firm Value.